Chronic cold-stress induced histopathological changes, oxidative stress, and alterations in liver functions and nutrient composition of hybrid red tilapia and the potential protection of unsaturated fatty acids - Refaey, Mohamed M.; Mehrim, Ahmed I.; El-Komy, Magda M.; Zenhom, Osama A.; Mansour, Abdallah Tageldein (Frontiers in Marine Science, 2023)
Hybrid red tilapia (Oreochromis niloticus × O. mossambicus) is a promising tilapia fish but is a sensitive species to low water temperature. Therefore, the purpose of this experiment was to improve the resistance of hybrid red tilapia against chronic-cold stress by increasing unsaturated fatty acids and evaluating their effects on fish body weight, hepatosomatic index (HSI), body nutrient composition, hepatic function enzymes, histopathology alterations, and oxidative stress biomarkers in gills and liver. Fish were fed four diets depending on two dietary fat sources, including corn oil (traditional source) and Aquafat-O® (commercial product rich in high polyunsaturated fatty acids) at different ratios of 3:0 (T0), 2:1 (T1), 1:2 (T2), and 0:3 (T3), respectively, for 98 days at a rearing water temperature of 25-26 ºC. After that, for 15 successive days, all groups (T0+, T1, T2, and T3) were exposed to water cold stress at 13 ºC, with maintaining half of the control group as a negative control (T0-), which was reared at a water temperature of 25-26 ºC. The exposure of hybrid red tilapia to cold stress caused significant reductions in fish body weight, HSI, fat and energy contents, aspartate transaminase, alanine transaminase activities, and oxidative stress biomarkers in the liver and the gills. Severe histopathological alterations in the gills and the liver were also reported in red tilapia exposed to low temperature. However, all the unfavorable effects of cold stress were gradually ameliorated with an increasing Aquafat-O® ratio in the diet. Thus, it could be concluded that the beneficial use of Aquafat-O® (as a promising fat source) up to a ratio of 69.60 g kg-1 diet to cope with the cold-water stress for sensitive hybrid red tilapia.